2
$\begingroup$

On page 252 of do Carmo's book "Differential Geometry of Curves and Surfaces" there is a proof given of the following proposition:

Let $x(u,v)$ be an orthogonal parametrization (that is, $F=0$) of a neighborhood of an oriented surface $S$, and $w(t)$ be a differentiable field of unit vectors along the curve $x(u(t), v(t))$. Then $$\left[\frac{Dw}{dt}\right]=\frac{1}{2\sqrt{EG}}\left\{G_u\frac{dv}{dt}-E_v\frac{du}{dt}\right\}+\frac{d\varphi}{dt}$$ where $\varphi(t)$ is the angle from $x_u$ to $w(t)$ in the given orientation.

Here is up to the relevant part the proof. I don't understand how the last equality in the below proof comes about. That equality is $\left\langle \left(\frac{x_u}{\sqrt{E}}\right)_u,\frac{x_v}{\sqrt{G}} \right\rangle=-\frac{1}{2}\frac{E_v}{\sqrt{EG}}$ and I don't see why the partial by $u$ on the left hand side does not effect the denominator $\sqrt{E}$ give that $E$ should be defined as $x_u \cdot x_u$

Proof. Let $e_1 = x_u/\sqrt{E}$, $e_2=x_v/\sqrt{G}$ be the unit vectors tangent to the coordinate curves. Observe that $e_1\wedge e_2=N$, where $N$ is the given orientation of $S$. By using Lemma 2, we may write $$\left[\frac{Dw}{dt}\right]=\left[\frac{De_1}{dt}\right]+\frac{d\varphi}{dt}$$ where $e_1(t)=e_1(u(t),v(t))$ is the field $e_1$ restricted to the curve $x(u(t),v(t))$. Now $$\left[\frac{De_1}{dt}\right]=\left\langle\frac{de_1}{dt},N\wedge e_1\right\rangle=\left\langle\frac{de_1}{dt},e_2\right\rangle=\left\langle(e_1)_u,e_2\right\rangle\frac{du}{dt}=\left\langle(e_1)_v,e_2\right\rangle\frac{dv}{dt}$$. On the other hand, since $F=0$, we have $$\langle x_{uu},x_v \rangle=-\frac{1}{2}E_v$$, and therefore $$\left\langle (e_1)_u,e_2 \right\rangle=\left\langle \left(\frac{x_u}{\sqrt{E}}\right)_u,\frac{x_v}{\sqrt{G}} \right\rangle=-\frac{1}{2}\frac{E_v}{\sqrt{EG}}$$

$\endgroup$
0
+250
$\begingroup$

Well, because $x_u \cdot x_v = 0$, so

\begin{align} \left\langle \left(\frac{x_u}{\sqrt{E}}\right)_u,\frac{x_v}{\sqrt{G}} \right\rangle&= \left\langle \frac{x_{uu}}{\sqrt E} + \left(\frac{1}{\sqrt E}\right)_u x_u, \frac{x_v}{\sqrt G}\right\rangle\\ & = \left\langle \frac{x_{uu}}{\sqrt E}, \frac{x_v}{\sqrt G}\right\rangle \end{align}

$\endgroup$
  • $\begingroup$ Oh I totally forgot about the orthogonal parametrization condition while reading the proof. $\endgroup$ – user782220 Sep 14 '18 at 17:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.